Stem Cell Trials for Cardiovascular Medicine: Ethical Rationale - Niemansburg, Sophie L. (Mary Ann Liebert, Inc., 2014)
Stem cell-based interventions provide new treatment prospects for many disease conditions, including cardiovascular disorders. Clinical trials are necessary to collect adequate evidence on (long-term) safety and efficacy of novel interventions such as stem cells, but the design and launch of clinical trials, from first-in-human studies to larger randomized controlled trials (RCTs), is scientifically and ethically challenging. Stem cells are different from traditional pharmaceuticals, surgical procedures, and medical devices in the following ways: the novelty and complexity of stem cells, the invasiveness of the procedures, and the novel aim of regeneration. These specifics, combined with the characteristics of the study population, will have an impact on the design and ethics of RCTs. The recently closed JUVENTAS trial will serve as an example to identify the (interwoven) scientific and ethical challenges in the design and launch of stem cell RCTs. The JUVENTAS trial has investigated the efficacy of autologous bone marrow cells in end-stage vascular patients, in a double-blind sham-controlled design. We first describe the choices, considerations, and experiences of the JUVENTAS team. Subsequently, we identify the main ethical and scientific challenges and discuss what is important to consider in the design of future stem cell RCTs: assessment of risks and benefits, the choice for outcome measures, the choice for the comparator, the appropriate selection of participants, and adequate informed consent. Additionally, the stem cell field is highly in the spotlight due to the (commercial) interests and expectations. This warrants a cautious pace of translation and scrupulous set up of clinical trials, as failures could put the field in a negative light. At the same time, knowledge from clinical trials is necessary for the field to progress. We conclude that in the scientifically and ethically challenging field of stem cell RCTs, researchers and clinicians have to maneuver between the Skylla of hyper accelerated translation without rigorously conducted RCTs and the Charybdis of the missed opportunity of valuable knowledge.